Anxiety, perceived mental healthcare need and coping strategies regarding COVID-19 pandemic among pre-university students at Bangalore: a cross-sectional study - A. V., Sowmya; Upashe, Shivaleela P.; R., Amitha; Bhutia, Chung; Hemalatha, B.; Kumari, T.; Jatti Patgar, Suvarna (International Journal Of Community Medicine And Public Health, 2025)
Background: Although the COVID-19 pandemic has declined, cases still occur in some countries, continuing to cause concern. This situation affects not only health but also academic progress especially among students. Public health measures such as social distancing, while necessary, have contributed to isolation, stress and anxiety, thereby significantly impacting global mental health. To assess the impact of the COVID-19 pandemic on anxiety, coping strategies and perceived mental health care needs among pre-university students. Methods: An institutional-based descriptive cross-sectional web survey was conducted in May to June 2020 among 30 pre-university students selected through non-probability convenience sampling. Students with internet access who were willing to participate were included, while those who were seriously ill or unable to cooperate were excluded. Data were collected online using Google Forms with a semi-structured questionnaire. Results: The results showed that the majority of pre-university students, 63.3% (n=19), demonstrated a high level of coping strategies, while 36.7% (n=11) had a moderate level. The overall mean score was 52.5 with a standard deviation of 5.8. No significant association was found between the levels of anxiety, perceived mental health care needs and coping strategies related to the COVID-19 pandemic with their selected demographic variables. Conclusions: Our study revealed that most pre-university students experienced high anxiety, with equally high perceived mental health care needs and coping strategies. To support psychological adaptation, students should have access to programs like seminars and team-building activities. Adopting proper coping methods, stress management skills and international guidelines can help mitigate stress and anxiety.